Effect of emergent non-thermal extraction technologies on bioactive individual compounds profile from different plant materials - Moreira, Sílvia A. (2018)
Extraction is the first step for isolation and purification of interesting bioactive compounds, by mixing of the plant material with an adequate solvent. Those bioactive compounds are, usually, secondary metabolites, such as phenolic acids and flavonoids which are present in closed insoluble structures, making its extraction a challenge. There are many different traditional extraction methods, such as Soxhlet, heat reflux, and maceration. Nevertheless, due to several disadvantages, they are being replaced by new methods, using emergent technologies, such as high hydrostatic pressure, ultrasounds, pulsed electric fields, and supercritical fluids. The use of novel technologies allows enhancing mass transfer rates, increasing cell permeability as well as increasing secondary metabolite diffusion, leading to higher extraction yields, fewer impurities on the final extract, extractions at room temperature with thermo-sensitive structures preservation, use of different non-organic solvents, low energy consumption, short operation time, and have no significant or lower effect on the structure of bioactive compounds. This paper aims to review the effect of the main emergent extraction technologies (high hydrostatic pressure, pulsed electric fields, ultrasounds, and supercritical fluid assisted) on the individual profile of bioactive compounds from plant material.